Analisis Faktor-Faktor Kesulitan Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas XI IPS Di SMAN 3 Muaro Jambi - Saputri, Annisa Oktaviani; Alvionita, Havizah; Ningrum, Lusiana (SJEE (Scientific Journals of Economic Education), 2024)
This research aims to find out what are the most dominant factors that influence students' learning difficulties in class XI Economics Subjects at SMAN 3 Muaro Jambi. The research method used in this research is a quantitative method using factorization analysis techniques for research variables. The research results show that the school factor remains the most important factor in implementing activities and interactions in teaching and learning activities, both in providing theoretical and practical material. The better the development of a school in providing the best for the learning carried out, the lower the students' learning difficulties will be.